Drying Crops with Solar Energy - Bueflow, F H (Annals of Arid Zone, 2016)
The drying of crops with solar heated air is possible and in many situations economically feasible. The equipment and suplies required are readily available and usually low in cost. By using the roofs of existing buildings as solar collectors, the expenditure are minimal. Research presently underway is beginning to provide information on optimum construction of solar crop drying systems and optimum operating procedures for them.